ANALISA KEMAMPUAN DAN EFEKTIVITAS PENGGUNAAN AUTOMATIC METER READING PADA KWH METER PELANGGAN TELKOMSEL-LBB121-A - Andi Syofian; Rizqi Gunawan (Ensiklopedia of Journal, 2022)
Along with the increase in electricity meter tariffs, various frauds in the use of electrical energy have emerged; such as, illegal use of electricity which takes electricity sources not on the measuring tool and electricity limiter by the user; besides, errors in the manual meter recording process which can cause losses. Furthermore, by using Automatic Meter Reading (AMR), the accuracy in recording electrical energy measurements can be more accurate; besides, this tool is able to detect any abnormality in the measurement of electrical energy usage calculations on the customer's electronic meter. Therefore, in this study the writers focused on took data on cases of abnormality in the measurement of electricity usage of customers on behalf of TELKOMSEL-LBB121-A where the customer's electrical energy consumption had decreased drastically and when it was checked it turned out that the voltage on the 3-phase kWh meter display. Moreover, in all three phases the voltage is 0V so that the reading of electricity consumption being 0. In this case, the customer has a total follow-up bill of 8,495.72 kWh with a rupiah value of Rp. 12,465,600,04,-Keywords: KWh Meter, AMR, Follow-up bills, Electricity meter tariff